Mammalian Target of Rapamycin Inhibitors Resistance Mechanisms in Clear Cell Renal Cell Carcinoma - Kornakiewicz, Anna; Solarek, Wojciech; F. Bielecka, Zofia; Lian, Fei; Szczylik, Cezary; M. Czarnecka, Anna (Current Signal Transduction Therapy, 2013)
Mammalian target of rapamycin (mTOR) is a kinase protein involved in PI3K/AKT signaling with a central role in the processes of cell growth, survival and angiogenesis. Frequent mutations of this pathway make upstream and downstream components novel targets for tailored therapy design. Two mTOR inhibitors – everolimus and temsirolimus - enable an increase in overall survival (OS) or progression-free survival (PFS) time in a treatment of renal cancer. Despite recent advances in renal cancer treatment, resistance to targeted therapy is common. Understanding of molecular mechanisms is the basis of drug resistance which can facilitate prediction of success or failure in combinational or sequential targeted therapy. The article provides current knowledge on the mTOR signaling network and gives insight into the mechanisms of resistance to mTOR inhibitors from the complex perspective of RCC biology. The mechanisms of resistance developed not only by cancer cells, but also by interactions with tumor microenvironment are analyzed to emphasize the role of angiogenesis in ccRCC pathogenesis. As recent studies have shown the role of PI3K/AKT-mTOR pathway in proliferation and differentiation of cancer stem cells, we discuss cancer stem cell hypothesis and its possible contribution to ccRCC resistance. In the context of drug resistance, we also elaborate on a new approach considering ccRCC as a metabolic disease. In conclusion we speculate on future developments in agents targeting the mTOR pathway taking into consideration the singular biology of ccRCC.
Keywords: clear cell renal cell carcinoma